Calistung-Based Smart Book Media to Increase Student Interest in Learning Mathematics - Salma Febrina Putri; Wahyudi Wahyudi; Arta Ekayanti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Low learning interest among Hulu Langat Guidance Studio students has been observed, prompting efforts to enhance engagement through innovative methods. This study investigates the effectiveness of Smart Book  media in increasing students' interest in learning. Employing a classroom action research approach, the study followed four stages: planning, implementation, observation, and reflection. Conducted at the Hulu Langat Guidance Studio in Malaysia, the study involved a sample of 10 students. Data were collected through observation and questionnaires over two research cycles, incorporating Smart Book  media. The findings revealed a significant improvement in students' learning interest following the implementation of Smart Book  media. Questionnaire results indicated that all students categorized their learning interest as "Very Interested" after using Smart Book  media. The results demonstrate that Smart Book  media effectively enhances student engagement by making the learning process more interactive and appealing. Smart Book  media is a valuable tool for increasing students' interest in learning, as evidenced by the positive outcomes of this study. Further research with larger samples and diverse contexts is recommended to validate these findings and explore broader applications of Smart Book  media.